Solving a system of nonlinear fractional partial differential equations using three dimensional differential transform method - Kurulay, Muhammet; Ibrahimoglu, Bayram Ali; Bayram, Mustafa (ACADEMIC JOURNALS, 2010)
In this article, three dimensional fractional partial differential transform method (FPDTM) has been employed to obtain solutions of a System of nonlinear fractional partial differential equations. This indicates the validity and great potential of the homotopy analysis method for solving system of fractional partial differential equations. Fractional differential transform method can easily be applied to nonlinear problems and reduces the size of computational work. With this method exact solutions may be obtained without any need of cumbersome work and it is a useful tool for analytical and numerical solutions. The fractional derivative is described in the caputo sense.
Keywords: Fractional partial differential transform method; Caputo fractional derivative; system of fractional partial differential equations; HOMOTOPY ANALYSIS METHOD; Science & Technology - Other Topics